2015
DOI: 10.1155/2015/742535
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Circulating T Follicular Helper Cells in Children with Acute Henoch-Schönlein Purpura

Abstract: Henoch-Schönlein purpura (HSP) is a common systemic small vessel vasculitis in children with disorder autoimmune responses. T follicular helper (TFH) cells play crucial roles in regulating immune responses. The aim of our study was to investigate the probable role of TFH cells in the pathogenesis of children with HSP. In this study, the frequency of circulating CXCR5+CD4+TFH cells with inducible costimulator (ICOS) expression in the children with acute HSP was significantly higher than that in healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
(58 reference statements)
4
14
0
Order By: Relevance
“…PD-1, a functional marker of Tfh cells, exhibited no differences in expression between the two groups. A similar nding reported an expansion of circulating Tfh cells in children with acute HSP; a signi cant increase in CXCR5 + CD4 + cells in children with HSP and no differences in PD-1 expression between two groups were noted (12). Moreover, correlations between Tfh cells and naïve B cells, and class-switched B cell subsets, as well as memory B cells, were found in children with HSP in our study.…”
Section: Discussionsupporting
confidence: 85%
“…PD-1, a functional marker of Tfh cells, exhibited no differences in expression between the two groups. A similar nding reported an expansion of circulating Tfh cells in children with acute HSP; a signi cant increase in CXCR5 + CD4 + cells in children with HSP and no differences in PD-1 expression between two groups were noted (12). Moreover, correlations between Tfh cells and naïve B cells, and class-switched B cell subsets, as well as memory B cells, were found in children with HSP in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, serum levels of IL-21, IL-6, IgA and C3 were also significantly higher in HSP children than in healthy controls. A positive correlation was observed between the frequency of circulating ICOS + CXCR5 + CD4 + Tfh cells and the serum levels of IL-21 or IgA (74). Additionally, mRNA expression levels of IL-21, IL-6 and Bcl-6 were also significantly increased in peripheral blood from children with acute HSP compared to healthy controls (74).…”
Section: Tfh Cellsmentioning
confidence: 90%
“…A positive correlation was observed between the frequency of circulating ICOS + CXCR5 + CD4 + Tfh cells and the serum levels of IL-21 or IgA (74). Additionally, mRNA expression levels of IL-21, IL-6 and Bcl-6 were also significantly increased in peripheral blood from children with acute HSP compared to healthy controls (74). Following treatment, the numbers of CD4 + CXCR5 + , CD4 + CXCR5 + PD-1 + and CD4 + CXCR5 + ICOS + Tfh cells, as well as serum levels of IL-21 were significantly reduced (75).…”
Section: Tfh Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…The expansion of circulating Tfh cells has been reported in various autoimmune diseases [ 19 , 21 ], suggesting their pathogenic significance. Xie et al revealed that the frequency of circulating CD4 + CXCR5 + ICOS + Tfh cells in children with active IgAV was significantly higher than in healthy children [ 22 ]. Wang et al also reported that the upregulation of circulating Tfh cells and downregulation of circulating follicular regulatory T (Tfr) cells may contribute to the pathogenesis of IgAV in children [ 23 ].…”
Section: Introductionmentioning
confidence: 99%